Effect of Combined Mental Task and Metaboreflex Activation on Hemodynamics and Cerebral Oxygenation in Patients With Metabolic Syndrome - Doneddu, Azzurrra; Roberto, Silvana; Pinna, Virginia; Magnani, Sara; Ghiani, Giovanna; Sainas, Gianmarco; Mulliri, Gabriele; Serra, Stefano; Kakhak, Seyed Alireza Hosseini; Milia, Raffaele; Lecis, Romina; Guicciardi, Marco; et al. (Frontiers in Physiology, 2020)
Objective: The hemodynamic response to muscle metaboreflex has been reported to be significantly altered by metabolic syndrome (MS), with exaggerated systemic vascular resistance (SVR) increments and reduced cardiac output (CO) in comparison to healthy controls (CTLs). Moreover, patients with metabolic disorders, such as type 2 diabetes, have proven to have impaired cerebral blood flow in response to exercise. Thus, we hypothesized that contemporary mental task (MT) and metaboreflex would result in reduced cerebral oxygenation (COX) in these patients. Methods: Thirteen MS patients (five women) and 14 normal age-matched CTLs (six women) were enrolled in this study. All the participants underwent five different tests, each lasting 12 min: post-exercise muscle ischemia (PEMI) to activate the metaboreflex, control exercise recovery (CER), PEMI + MT, CER + MT, and MT alone. Cerebral oxygenation was evaluated using near-infrared spectroscopy with sensors applied to the forehead. Hemodynamics were measured using impedance cardiography. Results: The main results show that MS patients had higher SVR and lower CO levels compared to the CTL group during metaboreflex activation. Stroke volume and ventricular filling and emptying rates were also significantly reduced. Moreover, when MT was added to PEMI, COX was significantly increased in the CTL group with respect to the baseline (103.46 ± 3.14%), whereas this capacity was reduced in MS patients (102.37 ± 2.46%). Conclusion: It was concluded that (1) patients with MS showed hemodynamic dysregulation during the metaboreflex, with exaggerated vasoconstriction and that (2) as compared to CTL, MS patients had reduced capacity to enhance COX when an MT superimposed the metaboreflex.